Undetectable negative tissue transglutaminase IgA antibodies predict mucosal healing in treated coeliac disease patients. Issue 7 (7th August 2017) - Fang, H.; King, K. S.; Larson, J. J.; Snyder, M. R.; Wu, T. T.; Gandhi, M. J.; Murray, J. A.
Summary: Background: Tissue transglutaminase (tTG) immunoglobulin A (IgA) testing is a sensitive adjunct to the diagnosis of coeliac disease. The threshold for positivity was developed for diagnosis, with negative results reported as below the reference value (<4 U/mL). Aim: To investigate if an undetectable (tTG IgA<1.2 U/mL) is more predictive of healing compared to patients with negative but detectable serology (1.2‐3.9 U/mL). Methods: We performed a retrospective study of 402 treated coeliac disease patients seen at the Mayo Clinic with negative tTG IgA values drawn within 1 month of duodenal biopsy between January 2009 and December 2015. The Corazza‐Villanacci score was used to assess mucosal healing. The presence of gastrointestinal symptoms was also collected. Logistic regression was used to assess the relationship of clinical variables with a normal biopsy. Results: Patients with undetectable titres more frequently had normal duodenal histology compared to patients with detectable tTG IgA levels (117/240 vs. 53/162; OR=1.96; 1.292, 2.961). Asymptomatic patients more frequently had normal duodenum as compared to symptomatic patients (88/163 vs. 82/239; OR=2.25; CI: 1.494, 3.377). Patients with undetectable serology and on a gluten‐free diet for ≥2 years were more likely to have no villous atrophy compared to patients with detectable serology (148/192 vs. 55/88; OR=2.02; CI: 1.17, 3.49). Conclusion: In subjects recovering from coeliac disease with negative tTG IgA serology, an undetectable titre is associated with normal histology on follow‐up biopsy. Abstract : Linked Content This article is linked to Din et al and Fang and Murray papers. To view these articles visithttps://doi.org/10.1111/apt.14287 andhttps://doi.org/10.1111/apt.14333 .